Survei efektifitas pembelajaran penjas di SD melalui daring se-kecamatan Petarukan Pemalang - Galih Dwi Pradipta; Osa Maliki; Maftukin Hudah (Journal of Physical Activity and Sports (JPAS), 2021)
The background of the problem is whether online learning for physical education subjects in elementary school can run effectively, physical learning is dominant by doing a lot of movement activities that must be followed by students, considering that in physical education learning motion learning must also be followed by supporting tools in practice. The Covid 19 pandemic changes face-to-face learning processes into a network, all processes are carried out without face to face directly. This underlies this research to determine whether physical education learning during the pandemic can be effective in delivering material. The research method was descriptive qualitative in which to obtain the data used a survey tool via google form which was distributed to elementary school physical education teachers in Petarukan sub-district, the number of primary schools taken for the study was 23 elementary schools and the sample of teachers in filling out google form was 27 PJOK teachers. The results showed that online physical education learning runs effectively, the level of effectiveness is influenced by the availability of internet networks, the knowledge of teachers and students in operating the learning system online through applications provided in online learning (WhatsApp, google meet), and students have the communication tools used. in online learning.